Reading Jibanananda Das’s “Banalata Sen” from a surrealistic perspective - Jahan, Sultana (IIUC Studies, 2018)
Surrealism expresses the working of the subconscious, as manifested in dreams and uncontrolled by reason and characterized by the incongruous and startling arrangement and presentation of subject matter. The theme of Jibanananda's poem ‗Banalata Sen' is straightforward. However, because of the style of presentation, it appeared to be subtle, mysterious and bizarre even to the native readers and critics of his time. The poet's wizardry of image and metaphor makes an ordinary Banalata Sen beyond touch as she transcends to a higher space, surpassing all worldly affairs. The poet presents her beauty in entirely different imagery infrequent in our literature before his utterance. Throughout the poem, he creates a sense of wonder and dreamlike progression from the flow of time expressed by ancient civilizations and illusory natural beauty to the contemplation of the end of earthly affairs. With a view to establishing Jibanananda's ‗Banalata Sen' as a surrealist poem, this article aims at exploring the images and metaphors that has unfolded his subliminal working of the mind. IIUC Studies Vol.13 December 2016: 83-92